Everyone loses the Ukraine crisis and the ruinous contest for post-Soviet Eurasia - Charap, Samuel 1980-; Colton, Timothy J. 1947- (Adelphi (Series) (International Institute for Strategic Studies), 2017)
Disorder erupted in Ukraine in 2014, involving the overthrow of a sitting government, the Russian annexation of the Crimean peninsula, and a violent insurrection, supported by Moscow, in the east of the country.